HUBUNGAN KEAKTIFAN SISWA DALAM KEGIATAN IKATAN PELAJAR MUHAMMADIYAH DENGAN HASIL BELAJAR AL-QUR’AN HADITS DI SMK MUHAMMADIYAH WATUKELIR - Rosyidah Nur ‘Aini; Edy Muslimin (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the relationship between students’ activeness in participating in the Ikatan Pelajar Muhammadiyah (IPM) student organization and their learning outcomes in Qur’an Hadith subject, focusing on 12th-grade Accounting students at SMK Muhammadiyah Watukelir in the 2024/2025 academic year. The research employed a quantitative correlational approach, using purposive stratified sampling to obtain a sample of 59 students. Organizational activeness data were collected via a questionnaire, while Qur’an Hadith learning outcomes were obtained from documentation of semester report card grades for 2024/2025. The questionnaire instrument was validated and tested for reliability prior to use. Prerequisite tests (normality and linearity) indicated non-normal data distribution; therefore, correlation analysis used Spearman’s Rank. The main results showed that students’ activeness in IPM activities was moderate on average (mean questionnaire score 69.32). Students’ Qur’an Hadith learning outcomes were good, with an average score of 96.32 (category B, moderate). The Spearman correlation test yielded a coefficient ρ = 0.158 with p = 0.232 (> 0.05), indicating no significant relationship between IPM activeness and Qur’an Hadith performance.